Pengaruh Fasilitas Kerja terhadap Pengelolaan Arsip di Kantor Satuan Polisi Pamong Praja Kabupaten Lombok Timur - Nova Hari Santhi; Ahyar Rosidi (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
Archives as a memory center and as a source of written information must be available when needed in order to provide effective service. Therefore, in managing archives, the archiving system must be considered with the state of the organization in achieving its goals. The effectiveness of archiving management is also influenced by employees working in the archiving unit, the facilities used and the funds available for maintaining archives. This study is a type of quantitative descriptive research, namely research that describes research variables using a quantitative approach. The population in this study were all Satpol PP employees 320. The sample in this study used a Nonprobability sampling sample, a sampling technique that does not provide the same opportunity/chance as the accidental sampling technique, namely anyone he meets becomes a sample. The number of samples in this study was 76 respondents. Data collection used a questionnaire method. The questionnaire method was carried out to obtain respondents' responses regarding work facilities and archiving management. Data analysis used to test the hypothesis in this study was using Simple Linear Regression analysis found in the SPSS v. 1.0 program. 19 The results of the study show that work facilities significantly influence archive management with a positive coefficient, which explains that there is a directly proportional relationship between the two variables. With the Regression Coefficient of the Work Facilities Variable (X1) of 0.949 with a sig value of 0.000, it illustrates that Work Facilities have a positive and significant influence on archive management, meaning that the more complete the work facilities owned by the agency, the easier it will be to manage its archives.